CF3Br plasma cryo etching of low-k porous dielectric. (August 2016) - Clemente, I; Koehler, N; Miakonkikh, A; Zimmermann, S; Schulz, S E; Rudenko, K
Abstract: Process of plasma etching of CVD low-k dielectric was studied. We used CF3 Br low pressure ICP plasma for etching at cryo temperatures (-20°C — -100°C), pressures (5-20 mTorr) and RF bias with effective DC voltage 80-140 V. Refractive index of film and its thickness were measured by spectral ellipsometry. Ellipsometric porosimetry was employed to compare pore size distribution before and after etching of films. Measurements show increasing of etch rate increase with decreasing sample temperature.